POSITIVE EFFECT OF ETHICAL BEHAVIOR, CORPORATE ETHICAL VALUE, AND IDEALISM IN THE WORKPLACE - Kathelyn Kathelyn; Andi Ina Yustina; Setyarini Santosa (Universitas Pakuan, 2019)
Accountants who work in a company that adopted an excellent corporate ethical value are believed to have a higher idealism orientation of ethics. This study empirically examines the role of ethical behavior to influence the positive effect of corporate ethical value toward an accountant's idealism. By using a web-based survey, this study spread 100 questionnaires to accountants in Indonesia. The statistical analysis that is used for this research is the Structural Equation Model (SEM) with a Partial Least Squares (PLS) approach. This study result shows that there is a positive relationship between corporate ethical value and idealism, moderate by ethical behavior.